Partitioning of calcium and magnesium (total divalent cations) during membrane filtration of milk - Lin, M.-J.; Grandison, A.S.; Lewis, M.J. (Journal of food engineering, 2015)
•This article investigates the partition of total divalent actions during the membrane processing of milk.•It compares RO, NF and UF and for UF looks at how partitioning is affected by pH and temperature.•The findings may be beneficial in terms of manipulating the mineral composition of milk to improve heat stability or other functional properties. Partitioning of total divalent cations (TDVC) during reverse osmosis (RO), nanofiltration (NF) and ultrafiltration (UF) has been investigated. During RO, there was an increase in TDVC and Ca2+, and a reduction in the ethanol stability of RO retentates. During UF of milk at its normal pH, there was an increase in total divalent cations, but only a slight increase in Ca2+ in the retentate. There was some loss of micellar calcium during UF. However, the ratio of amounts of soluble to total divalent cations in the retentate decreased as concentration factor increased. During NF, a small amount of TDVC was found in the permeate and TDVC rejection was estimated to be about 0.83. During UF of milk, the amount of TDVC in permeate increased significantly as the pH was reduced over the range 6.7–5.1 and the concentration of Ca2+ also increased both in the retentate and the permeate. However, this was not reversible, as when milk was restored to its original pH, its Ca2+ remained higher and ethanol stability was lower. In contrast, for whey and for UF permeate, changes in Ca2+ were reversible, when they were subject to similar pH changes. During UF, TDVC concentration in permeate decreased as temperature increased, due to the lower solubility of calcium phosphate at higher temperature. Ca2+ in permeate also decreased as UF temperature increased.